Analysis of the Effectiveness of the Online Single Submission (OSS) System at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of West Java Province - Pijar Indah Puspita Dewi; Heni Nurani Hartikayanti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effectiveness of the Online Single Submission (OSS) system implementation in business licensing services at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of West Java Province. The OSS system was introduced as a digitalization effort to improve efficiency, transparency, and ease of doing business. However, business actors' compliance with submitting the Investment Activity Report (LKPM) remains low. Of the 26,947 companies with Business Identification Numbers (NIB) in West Java, only 37.9% submitted LKPM. This research uses a descriptive qualitative approach through interviews, observations, and document studies. The findings reveal that the quality of the OSS system, information, and services is relatively good; however, technical issues and users’ lack of understanding remain major obstacles. Intensive socialization, user training, and improvements in system infrastructure are key recommendations to enhance OSS effectiveness and encourage investment growth in the region. These findings offer practical insights for improving the management of information systems for licensing at the regional government level.